DEVELOPMENT OF INDICATION SYSTEM OF MOBILE ULTRASONIC SURGICAL INSTRUMENT - Bazilo, Constantine; Lavdanskyi, Artem; Zaika, Vasyl (Вісник Черкаського державного технологічного університету, 2019)
Prevalence of gunshot wounds in modern world is associated with criminalization of society, terrorist threats, increase of a number of local military conflicts and civil unrest. The search and development of methods for reducing blood loss, accelerating the healing of postoperative wounds and scars resorption is an important task of modern surgery, the solution of which is facilitated by the use of ultrasound. The use of ultrasonic surgery in military medicine and the use of piezoelectric elements as the source of ultrasound are perspective. Primary surgical treatment of wounds is the main method of preventing the development of severe infectious complications of gunshot wounds. When using an ultrasonic surgical instrument, an urgent task is to disinfect it before and after the operation. The purpose of this work is to develop an indication system for a mobile ultrasonic surgical instrument. A monochrome OLED display is used to indicate the state and interaction with the user in a mobile ultrasonic surgical instrument. STM32 series microcontroller is used to work with the display. The indication system provides a display of the current value of power, time and battery charge. The following items of adjusting menu are available: frequency, power, sterilization, clock, information. The power value is presented in percent as a scale from 0 % to 100 %. The sterilization time of adjusting menu provides a maximum sterilization time of 99 minutes and 59 seconds. The handle of the surgical instrument has all basic control elements for ease of use and simplicity. Proposed surgical instrument is mobile and can be used in extreme conditions. It does not require the use of a power cord. Li-ion batteries are used to ensure the mobility of the instrument. This work has been made within the framework of a state budgetary research topic “Development of mobile highly effective ultrasonic surgical instrument for military and civil medicine”